2021
DOI: 10.1051/e3sconf/202128402009
|View full text |Cite
|
Sign up to set email alerts
|

Application of innovative technologies in agriculture of Uzbekistan

Abstract: The issues of the development of innovative processes in agriculture in Uzbekistan on the example of the Tashkent province were revealed in this paper. The assimilation and further widespread dissemination of innovations are becoming key factors in the growth of production and employment in agriculture. It is here that the most significant reserves for improving product quality, saving labor and material costs, increasing labor productivity, improving the organization of production and increasing its efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 3 publications
0
17
0
1
Order By: Relevance
“…Thus, the study of the features of the physico-chemical characteristics of local varieties of lentil grains made it possible to determine the main directions of their industrial processing in order to obtain products of high quality and nutritional value (Table 4). The second experiment was dedicated to determined physico-chemical and functional properties of a protein isolate from lentil grain (PILG), which is given in Table 5, which also provides literature data [8,9] for industrially produced soy protein isolates. The experimental data showed that the studied protein isolate from lentil grain was characterized by high values of a number of functional properties and can be used as an emulsifier, foaming agent, as well as to increase the water and fat-retaining ability of food systems.…”
Section: -Heterogeneousmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the study of the features of the physico-chemical characteristics of local varieties of lentil grains made it possible to determine the main directions of their industrial processing in order to obtain products of high quality and nutritional value (Table 4). The second experiment was dedicated to determined physico-chemical and functional properties of a protein isolate from lentil grain (PILG), which is given in Table 5, which also provides literature data [8,9] for industrially produced soy protein isolates. The experimental data showed that the studied protein isolate from lentil grain was characterized by high values of a number of functional properties and can be used as an emulsifier, foaming agent, as well as to increase the water and fat-retaining ability of food systems.…”
Section: -Heterogeneousmentioning
confidence: 99%
“…Recently, special attention has been paid to the processing of lentil grains, which are a source for obtaining protein isolate [7]. Local varieties of lentils are valued for their high protein content [8][9][10], containing a large amount of essential amino acids that are important for the human organism [11,12]. In this regard, the study of the structure and properties of proteins of local varieties of lentils is an urgent issue.…”
Section: Introductionmentioning
confidence: 99%
“…Os clusters de negócios não conseguiram interagir do ponto de vista legal, económico e organizacional, ameaçando as empresas baseadas na agricultura. O país não conseguiu definir o cluster da melhor forma possível para evitar complicações indesejadas (NARINBAEVA G. et al 2021). A nação carece de princípios para formar previsões para desenvolver parâmetros de seleção de empresas e clusters agrícolas regionais em que devem participar.…”
Section: A Problemaunclassified
“…Livestock is one of the leading sectors of agriculture in Uzbekistan [1]. Meat, dairy and egg products of the population provide the industry with leather, wool and other raw materials.…”
Section: Introductionmentioning
confidence: 99%